Rituximab is highly effective in children and adolescents with Burkitt lymphoma in Risk Groups R2 to R4. (17th August 2020) - Zhen, Zijun; Zhu, Jia; Wang, Juan; Lu, Suying; Sun, Feifei; Huang, Junting; Sun, Xiaofei
Abstract: Data regarding the use of rituximab in children and adolescents with Burkitt's lymphoma (BL) is limited. This study retrospectively analyzed the effect of rituximab on children and adolescents with BL in risk group (R) 2 to R4. Patients underwent chemotherapy according to the revised NHL-BFM-95 protocol. Rituximab was administered at the dose of 375 mg/m 2 on day 0 of each cycle. A total of 106 patients were included. Stratified by the number of doses of rituximab, there were 49, 16, and 41 patients in group 1 (no rituximab), group 2 (1–3 doses of rituximab) and group 3 (≥4 doses of rituximab), respectively. The 3-year event-free survival (EFS) rates were 83.2% (95% CI = 72.6%–93.8%), 81.2% (95% CI = 52.3%–93.5%) and 96.8% (95% CI = 78.8%–99.6%) in group 1, group 2 and group 3, respectively ( p = 0.077). In R2/R3, the relapse rates were 0 in patients treated with rituximab and 11.8% in those treated without rituximab ( p = 0.516). In R4, the relapse rates were 18.8%, 21.4% and 3.0% in group 1, group 2 and group 3, respectively ( p = 0.048). Rituximab is highly effective in children and adolescents with BL in R2 to R4. The optimal number of doses was 4–6 in patients with BL in R4.